The Implementation of Islamic Value Absorption in Regional Regulations in Madura Regency - Agung Ali Fahmi; Muwaffiq Jufri; Ansori Ansori (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2020)
In Madura, a number of Sharia and / or sharia nuances Regional Regulations were born. Whereas, Indonesia is not a religious state. The emergence of such Regional Regulations is believed to cause a lot of conflict in the society. Therefore, it is necessary to know How is the legal politics of values absorption or Sharia legal provisions in the Regional Regulations of Madura Regency? This research is a normative legal research. This research includes a conceptual approach, a statutory approach, and a case approach. The finding shows that the application and / or absorption of Sharia in Madura are due to the religious values that attached in the societies' daily life. So after conducting the research, it is found that the application and / or absorption of the Islamic values in regional legal products in Madura are divided into two types; firstly; direct absorption and / or application of regional legal products, in the form of Perda or Perbup. Secondly, the absorption and / or application of Islamic legal values to regional legal products do not directly manifest the sharia legal products, but substantially, the material contained in the legal products has absorbed the Islamic values into it.